2010
DOI: 10.1029/2010gl045696
|View full text |Cite
|
Sign up to set email alerts
|

Biological regime shifts and changes in predictability

Abstract: Time series of climate indices and of biomass, abundance, and species number of benthic macrofauna in the southern North Sea are related to each other to investigate the predictability of biological time series in presence of biological regime shifts in 1989/1990 and 2001/2002. The results indicate that a smooth biological regime shift occurred in 1989/1990 caused by positive climate feedback mechanisms. In this case, the benthic community structure remained predictable. In contrast, in 2001/2002 an abrupt bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
(53 reference statements)
2
29
0
Order By: Relevance
“…NAO has long been considered as a very good predictor in forecasting benthic time series (Kröncke, 2011). However, after the regime shift in 2000/2001 the correlation between NAO and macrofauna biomass and abundance diminished, perhaps reflecting the disappearance of autocorrelation and thus predictability (Dippner et al, 2010;Junker et al, 2012;Kröncke et al, 2013). Presumably, this may be the reason that the DFM exhibited the highest AIC when we consider NAOWI as the only explanatory variable.…”
Section: Relative Contribution Of Explanatory Variablesmentioning
confidence: 90%
“…NAO has long been considered as a very good predictor in forecasting benthic time series (Kröncke, 2011). However, after the regime shift in 2000/2001 the correlation between NAO and macrofauna biomass and abundance diminished, perhaps reflecting the disappearance of autocorrelation and thus predictability (Dippner et al, 2010;Junker et al, 2012;Kröncke et al, 2013). Presumably, this may be the reason that the DFM exhibited the highest AIC when we consider NAOWI as the only explanatory variable.…”
Section: Relative Contribution Of Explanatory Variablesmentioning
confidence: 90%
“…This might be perhaps the case in terrestrial ecosystems considered by Hallett et al (2004). But, our results indicated that this is surely not the case in marine areas such as the North Sea (Dippner et al 2010) and the Baltic Sea (Möllmann et al 2009). Our results indicate that the multivariate BSE index combined of large-and regional-scale indices has an excellent performance and a high versatility much better than each single large-scale index only.…”
Section: Discussionmentioning
confidence: 57%
“…copepodite and T. longicornis copepodite spring biomass anomaly observed and predicted using the BSE index and Chen index. The observation indicates a negative biomass anomaly from 1960 until the 1989/1990 regime shift (Dippner et al 2010). Amplitude and trends are well reproduced by the BSE index including the 1989/1990 regime shift, whereas the amplitudes reproduced by the Chen index are too small.…”
Section: Performance Test With Biological Datamentioning
confidence: 88%
See 2 more Smart Citations